2020
DOI: 10.3389/fcell.2020.00540
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-138-5p Suppresses Non-small Cell Lung Cancer Cells by Targeting PD-L1/PD-1 to Regulate Tumor Microenvironment

Abstract: Non-small cell lung cancer (NSCLC) is still challenging for treatment owing to immune tolerance and evasion. MicroRNA-138 (miR-138) not only acts as a tumor suppressor to inhibit tumor cell proliferation and migration but also regulates immune response. The regulatory mechanism of miR-138 in NSCLC remains not very clear. Herein, we demonstrated that miR-138-5p treatment decreased the growth of tumor cells and increased the number of tumor-infiltrated DCs. miR-138-5p not only down-regulated the expression of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…We found by microarray analysis that miR-138-5p was upregulated in usual PSCC. miR-138-5p is a tumor suppressor that targets PD-L1 [ 70 , 71 , 72 ]. Therefore, it would be interesting to investigate the potential role of miR-138-5p as a biomarker for therapy selection using checkpoint inhibitors in PSCC patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We found by microarray analysis that miR-138-5p was upregulated in usual PSCC. miR-138-5p is a tumor suppressor that targets PD-L1 [ 70 , 71 , 72 ]. Therefore, it would be interesting to investigate the potential role of miR-138-5p as a biomarker for therapy selection using checkpoint inhibitors in PSCC patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, miR-138-5p could target PDL1 to inhibit tumorigenesis in colorectal cancer and lung cancer (Zhao, Yu et al, 2016;Song, Li et al, 2020). Ashizawa et al also revealed a regulatory mechanism of PDL1 expression that miR-148a-3p decreased PDL1 expression and suppressed immune evasion in colorectal cancer cells (Ashizawa, Okayama et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…As miR-25-5p may be sponged via phenanthriplatin-mediated upregulation of lnc-MRPL39-10 (Table 2), this miRNA could be downregulated in A549 cells, which is associated with anti-cancer effect via PI3K signaling [25]. Reduction of AGO2-1, COX7A1-2, and SLC26A3-1 by phenanthriplatin would also be expected to lead to increased miR-138-5p and − 608, whose expression modulates PTEN/PI3K/AKT signaling and is associated in A549 cells with anticancer effect [23,31,[45][46][47]. In retinoblastoma tumors, increased miR-4516 expression promotes tumor growth through the PTEN/AKT pathway [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-138-5p and miR-608 are potentially not subject to sponging in A549 cells treated with the monofunctional complex as their lncRNA targets are downregulated, but in IMR90 cells, these miRNA could be sponged by upregulated lnc-TMEM243-1 (Table 2, 3, 4). Therefore, reduced expression of miR-138-5p and − 608 due to TMEM243-1 decoying in IMR90 cells could lead to reduced cytotoxicity via TGF-β signaling (miR-138-5p) or Wnt/β-catenin and TGF-β signaling (miR-608) as suggested by the effects of suppressing these miRNAs in A549 cells [23,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%